Updated meta-review of evidence on support for carers - Sian Thomas; Jane Dalton; Melissa Harden; Alison Eastwood; Gillian Parker (National Institute for Health Research, 2017)
Background: Policy and research interest in carers continues to grow. A previous meta-review, published in 2010, by Parker et al. (Parker G, Arksey H, Harden M. Meta-review of International Evidence on Interventions to Support Carers. York: Social Policy Research Unit, University of York; 2010) found little compelling evidence of effectiveness about specific interventions and costs. Objective: To update what is known about effective interventions to support carers of ill, disabled or older adults. Design: Rapid meta-review. Setting: Any relevant to the UK health and social care system. Participants: Carers (who provide support on an unpaid basis) of adults who are ill, disabled or older. Interventions: Any intervention primarily aimed at carers. Main outcome measures: Any direct outcome for carers. Data sources: Database searches (including Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, MEDLINE, Applied Social Sciences Index and Abstracts and Social Care Online) for systematic reviews published from January 2009 to 2016. Review methods: We used EndNote X7.4 (Thomson Reuters, CA, USA) to screen titles and abstracts. Final decisions on the inclusion of papers were made by two reviewers independently, using a Microsoft Excel® 2013 spreadsheet (Microsoft Corporation, Redmond, WA, USA). We carried out a narrative synthesis structured by patient condition and by seven outcomes of interest. We assessed the quality of the included systematic reviews using established criteria. We invited a user group of carers to give their views on the overall findings of our review. Results: Sixty-one systematic reviews were included (27 of high quality, 25 of medium quality and nine of low quality). Patterns in the literature were similar to those in earlier work. The quality of reviews had improved, but primary studies remained limited in quality and quantity. Of the high-quality reviews, 14 focused on carers of people with dementia, four focused on carers of those with cancer, four focused on carers of people with stroke, three focused on carers of those at the end of life with various conditions and two focused on carers of people with mental health problems. Multicomponent interventions featured prominently, emphasising psychosocial or psychoeducational content, education and training. Multiple outcomes were explored, primarily in mental health, burden and stress, and well-being or quality of life. Negative effects following respite care were unsupported by our user group. As with earlier work, we found little evidence on intervention cost-effectiveness. No differences in review topics were found across high-, medium- and low-quality reviews. Limitations: The nature of meta-reviews precludes definitive conclusions about intervention effectiveness, for whom and why. Many of the included reviews were small in size and authors generally relied on small numbers of studies to underpin their conclusions. The meta-review was restricted to English-language publications. Short timescales prevented any investigation of the overlap of primary studies, and growth in the evidence base since the original meta-review meant that post-protocol decisions were necessary. Conclusions: There is no 'one size fits all' intervention to support carers. Potential exists for effective support in specific groups of carers. This includes shared learning, cognitive reframing, meditation and computer-delivered psychosocial support for carers of people with dementia, and psychosocial interventions, art therapy and counselling for carers of people with cancer. Counselling may also help carers of people with stroke. The effectiveness of respite care remains a paradox, given the apparent conflict between the empirical evidence and the views of carers. Future work: More good-quality, theory-based, primary research is warranted. Evidence is needed on the differential impact of interventions for various types of carers (including young carers and carers from minority groups), and on the effectiveness of constituent parts in multicomponent programmes. Further research triangulating qualitative and quantitative evidence on respite care is urgently required. The overlap of primary studies was not formally investigated in our review, and this warrants future evaluation. Study registration: This study is registered as PROSPERO CRD42016033367. Funding: The National Institute for Health Research Health Services and Delivery Research programme.